Phenotyping of Chronic Obstructive Pulmonary Disease Using the Modified Bhalla Scoring System for High-Resolution Computed Tomography - Baykal Tulek; Ali Sami Kivrak; Seda Ozbek; Fikret Kanat; Mecit Suerdem (Canadian Respiratory Journal)
BACKGROUND: Identifying different phenotypes of chronic obstructive pulmonary disease (COPD) is important for both therapeutic options and clinical outcome of the disease.